Dynamic kinetic resolution: Diastereoselective amination of alpha-halo esters and alpha-halo imidazolidinones. - O'Meara, Jeffrey A. (University of Ottawa (Canada), 1995)
The synthesis of optically active N-protected $\alpha$-amino esters and $\alpha$-amino imidazolidinones via a dynamic kinetic resolution protocol will be discussed. The methodology is based on fundamental reactivity differences between diastereomeric $\alpha$-halo esters and $\alpha$-halo imidazolidinones. The process involves nucleophillic displacement of the diastereomeric $\alpha$-halogenated esters and imidazolidinones with benzylamine. The corresponding displacement products are obtained with 70 - $>$ 98% de. Both absolute configurations are possible at the aminated postion by appropriate choice of the chiral auxiliary. The application of this methodology towards the synthesis of several optically active $\alpha$-amino esters was investigated. A five step sequence, starting from commercially available acid chlorides, was developed for synthesizing $\alpha$-amino esters in $\sim$40% overall yield. By utilizing dibenzylamine as the nucleophile, the DKR process has been effectively utilized in an approach to Reetz aldehydes ($\alpha$-dibenzylamino aldehydes). The increased bulk of dibenzylamine provides increased diastereoselectivity relative to benzylamine and the Reetz aldehyde precursors are obtained with a high degree of optical purity. Mechanistic aspects the reaction will also be discussed.
Keywords: Chemistry, Organic.